Implementasi Pembelajaran Metode Karya Wisata di Kuttab Ibnu Abbas Ngargoyoso Karanganyar - Sanusi, M.; Fauzi, Sriyono (TSAQOFAH, 2024)
This article discusses the application of the Work Tour Method in increasing students' faith, knowledge and enthusiasm for learning. The aim is to examine the learning process and the factors that influence its success. This research uses a qualitative descriptive approach with data collection techniques through interviews and documentation. The implementation of the Tourism Work Method learning at Kuttab Ibnu Abbas has proven to be able to strengthen students' faith, knowledge and enthusiasm for learning. However, care must be taken in its implementation, proportional and not excessive. The findings show that the Tourism Work Method is a method of supporting learning at Kuttab Ibnu Abbas in achieving its vision and mission, to become an educational institution that is faithful and devout, obedient to Allah subhanahu wa ta'ala and also His Messenger sallallaahu 'alaihi wa sallam, proficient in science syar'i and science, and have skills that suit the talents and interests of students.